Cloning of a passage-free SARS-CoV-2 genome and mutagenesis using red recombination - Herrmann, Alexandra; Jungnickl, Doris; Cordsmeier, Arne; Peter, Antonia Sophia; Überla, Klaus; Enßer, Armin (International Journal of Molecular Sciences, 2021)
The ongoing pandemic coronavirus (CoV) disease 2019 (COVID-19) by severe acute respiratory syndrome CoV-2 (SARS-CoV-2) has already caused substantial morbidity, mortality, and economic devastation. Reverse genetic approaches to generate recombinant viruses are a powerful tool to characterize and understand newly emerging viruses. To contribute to the global efforts for countermeasures to control the spread of SARS-CoV-2, we developed a passage-free SARS-CoV-2 clone based on a bacterial artificial chromosome (BAC). Moreover, using a Lambda-based Red recombination, we successfully generated different reporter and marker viruses, which replicated similar to a clinical isolate in a cell culture. Moreover, we designed a full-length reporter virus encoding an additional artificial open reading frame with wild-type-like replication features. The virus-encoded reporters were successfully applied to ease antiviral testing in cell culture models. Furthermore, we designed a new marker virus encoding 3xFLAG-tagged nucleocapsid that allows the detection of incoming viral particles and, in combination with bio-orthogonal labeling for the visualization of viral RNA synthesis via click chemistry, the spatiotemporal tracking of viral replication on the single-cell level. In summary, by applying BAC-based Red recombination, we developed a powerful, reliable, and convenient platform that will facilitate studies answering numerous questions concerning the biology of SARS-CoV-2.
CRIS-Team Scopus Importer:2021-10-01
Keywords: Bacterial artificial chromosome; COVID-19 pandemic; Incoming viral particles; Recombinant virus; Red recombination; Reporter virus; Reverse genetics; SARS-CoV-2